Enhancing entrepreneurship education in a master's degree in computer engineering: A project-based learning approach - Enrique Arias; Virginia Barba-Sánchez; Carmen Carrión; Rafael Casado (Administrative Sciences, 2018)
New master's degrees in computer engineering, designed according to Spanish government requirements, include both technical and business subjects to provide advanced knowledge compared to undergraduate studies. In spite of acquiring this advanced knowledge, our students are not always aware of the significant added value and the positive elements the master's degree provides for their future professional careers. Moreover, we have observed that students regard the different subjects as isolated blocks of knowledge. To tackle these problems, we have carried out a learning experience based on the creation of a technology-based enterprise (TBE) through the development of a common project (CP). Drawing on project-based learning (PBL) methodology, the CP consists of the identification, development, and final oral presentation of a business model. It aims to utilize sensor data and analysis in different domains. The experience has been highly positive, reducing the gap between studies and business practice, and increasing coordination among teachers. A key issue is that all the subjects of the master's degree are involved in this learning experience. In addition, results show a high level of satisfaction with the master's degree, compared to other similar courses.
Keywords: 350; entrepreneurship education; active learning; computer science; master's degree education; project-based learning (PBL); technology-based enterprise (TBE)